Refrigeration Technology Utilizing Engine Waste Heat in Fishing Vessels - Chen Shaojie; Chen Guangming (Zhileng xuebao)
Ice and compression refrigeration are normally used to preserve caught fish on fishing vessels. At the same time, waste heat dissipated in hot exhaust gas on fishing vessels is rejected to the atmosphere. Utilizing the vast amount of the waste energy for refrigeration is both economical and energy saving. Three kinds of heat driven refrigeration cycles as adsorption, absorption and ejection are introduced in this paper. Advantages and disadvantages of the three cycles are analyzed based on the working condition of ice making on fishing vessels. Emphases have been made on the feasibility of transforming the existing compression refrigeration cycle on fishing vessels by ejection technology. The result shows that 54.5% of fuel for refrigeration system can be saved after combining ejection and compression cycle and the transforming cost can be recovered in 1 year.